Covid Pictures. Reflections on the resulting emotionality - Coll Espinosa, Francisco Jesús (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2021)
The Covid-19 pandemic is not only being devastating in terms of economic development, but, fundamentally, in the experience of our experience of the intimate and social, affective and family reality. What we want to call the new reality implies a psychic and emotional decontextualization that forces us to reconstruct and re-signify our living presence in others. We are in dire need of the creation of new ways of developing ties, so that we continue to have otherness as the nodal element that sustains human relationships. For this, the contribution of art, creativity and creative therapies are living and indispensable mechanisms in this new reality.